2010
DOI: 10.1096/fj.10-155762
|View full text |Cite
|
Sign up to set email alerts
|

p21cip/WAFis a key regulator of long-term radiation damage in mesenchyme-derived tissues

Abstract: This study aimed to determine the mechanisms responsible for long-term tissue damage following radiation injury. We irradiated p21-knockout (p21(-/-)) and wild-type (WT) mice and determined the long-term deleterious effects of this intervention on mesenchyme-derived tissues. In addition, we explored the mechanisms of radiation-induced mesenchymal stem cell (MSC) dysfunction in isolated bone marrow-derived cells. p21 expression was chronically elevated >200-fold in irradiated tissues. Loss of p21 function resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
4
15
1
Order By: Relevance
“…To circumvent these difficulties, we used two different mouse models to study the effects of variable degrees of lymphatic injury on IL-6 expression. We have previously shown that ALND in mice results in significant but subtle increases in arm volume peaking at 3 wk and returning to normal by 6 wk (24,39). In this model, similar to clinical findings after lymphadenectomy, the ipsilateral limb is essentially normal in appearance by 6 wk.…”
Section: Discussionsupporting
confidence: 77%
“…To circumvent these difficulties, we used two different mouse models to study the effects of variable degrees of lymphatic injury on IL-6 expression. We have previously shown that ALND in mice results in significant but subtle increases in arm volume peaking at 3 wk and returning to normal by 6 wk (24,39). In this model, similar to clinical findings after lymphadenectomy, the ipsilateral limb is essentially normal in appearance by 6 wk.…”
Section: Discussionsupporting
confidence: 77%
“…ASCs were characterized for expression of known MSC markers (Sca1, CD29, CD73 and CD105) and absence of hematopoietic cell markers (CD34, CD45 and CD31) using our previously described flow cytometry techniques [21,22]. Briefly, cells were trypsinized, washed and 1 × 10 6 cells were incubated with fluorescent-tagged primary antibodies (from eBioscience; catalogue numbers as follows: Sca1 17-5981–81, CD29 12-0291-81, CD73 12-0731-81, CD105 12-1051-81, CD34 12-0341-81, CD45 15-045-81 [San Diego, CA, USA]; and CD31 from Biolegend [San Diego, CA, USA]) for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In order to analyze the pluripotential differentiation capacity of harvested ASCs, we induced bone, fat and cartilage differentiation using our previously published techniques [22,23]. Briefly, bone differentiation was induced by exposing cells to MesenCult ® stem cell media supplemented with 5 mM β-glycerophosphate, 10 −8 M dexamethasone and 0.28 mM ascorbic acid (all from Sigma-Aldrich, St Louis, MO, USA) for 14 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteins are of interest according to their function in cartilage homeostasis and/or differentiation. The cyclin-dependent kinase inhibitor (CKI) p21 has been associated with cellular senescence in different cell lines (8) and plays a major role in the regulation of long-term radiation damage in mesenchymederived tissues (9). Furthermore, H2A.J has recently been described as a novel histone variant accumulating in human senescent cells (10), and cyclooxygenase-2 (COX-2) protein has been associated with chondrocyte differentiation (11).…”
Section: Introductionmentioning
confidence: 99%